Pelatihan Pemanfaatan Basis Data Aplikasi Buku Tamu Bagi Perangkat Desa Cipta Karya - Yuliana, Yuliana; Mira, Mira; Charley, Charley (STMIK Royal, 2023)
Ciptakarya Village has an official village website as an information center and means of publishing all the potential that exists in the Village. Continuing the ongoing dedication to website development, data is then needed to develop a Database System on the web profile of the Cipta Karya village. This service activity aims to empower village officials through introduction and assistance in introducing the importance of Database management in the Guestbook application. In carrying out this service activity, the methods applied are 1) Socialization of activities, 2 Presentation of material by recognizing the basic benefits of data, 3) Training and assistance in using the guest book application, 4) Evaluation. The result of this service activity is a guest book application for the creative work village in managing data on visitors who visit the village office.Keywords: database; guest book; village apparatus Abstrak: Desa Ciptakarya memiliki website resmi desa sebagai pusat informasi dan sarana publikasi semua potensi yang ada di Desa. Melanjutkan pengabdian yang berjalan pada pengembangan website, maka selanjutnya dibutuhkan data dalam melakukan pengembangan Sistem Basis Data pada web profile desa cipta karya. Kegiatan pengabdian ini bertujuan untuk memperdayakan perangkat desa melalui pengenalan dan pendampingan dalam mengenal pentingnya pengelolaan Basis Data dalam aplikasi Buku Tamu. Dalam pelaksanaan kegiatan pengabdian ini metode yang diterapkan adalah 1) Sosialisasi kegiatan, 2)Pemaparan materi dengan mengenal manfaat basis data 3)Pelatihan dan pendampingan penggunaan aplikasi buku tamu, 4) Evaluasi. Hasil dari kegiatan pengabdian ini adalah aplikasi buku tamu untuk desa cipta karya dalam mengelola data pengunjung yang berkunjung di kantor desa.Kata kunci: basis data; buku tamu; perangkat desa